Night-eating syndrome and the severity of self-reported depressive symptoms from the Korea Nurses' Health Study: analysis of propensity score matching and ordinal regression. (December 2016) - Kim, O.-S.; Kim, M.S.; Lee, J.E.; Jung, H.
Abstract: Objectives: The prevalence of night-eating syndrome (NES) and depression is increasing worldwide. Although nurses, in particular, are exposed to work in an environment of irregular eating, shift work, and stressful settings, limited research exist. In fact, the prevalence of NES among Korean nurses has never been reported. The aim of this study was to determine the prevalence of NES as well as the association between NES and severity of self-reported depressive symptoms among South Korean female nurses. Study design: The Korea Nurses' Health Study, following the protocols of the Nurses' Health Study led by the Harvard University, collected data on Korean female nurses. Survey responses from 3617 participants were included, and 404 responses were analyzed in this cross-sectional study using propensity score matching. Methods: Descriptive, Spearman's and Cramer's correlations, propensity score matching, and multivariable ordinal logistic regression were conducted as statistical analysis. Results: The prevalence of both NES and self-reported depressive symptoms among Korean female nurses were higher compared with nurses in prior studies. Nurses with NES were 1.65 times more likely to have greater severity of depressive symptoms than those without NES (95% confidence interval [1.19–2.10], odds ratio = 1.65) after adjusting for covariates including sociodemographic characteristics, health behavioural factors, and shift work. Conclusion: This study suggests significant association between NES and the severity of self-reported depressive symptoms among Korean female nurses after adjusting for covariates. Policy makers and hospital managers need to develop strategies to reduce depression and NES among nurses for enhancement of nurses' mental and physical health as well as for improvement of care quality. Highlights: This is the first nationwide large sample study to report prevalence of night-eating syndrome (NES) among South Korean women, especially nurses. This is the first study to report on the association between NES and depressive symptoms among South Korean nurses. For conditions like eating disorders, there are issues with unequal sample sizes. We used propensity score matching (PSM) to reduce bias from skewed samples between two groups (NES and non-NES). Instead of using a binary-dependent variable, we investigated five levels of self-reported depressive symptoms using multivariable ordinal logistic regression analysis.